2022
DOI: 10.1111/joim.13440
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the blood–brain barrier in the treatment of brain tumours

Abstract: Brain tumours have a poor prognosis and lack effective treatments. The blood-brain barrier (BBB) represents a major hurdle to drug delivery to brain tumours. In some locations in the tumour, the BBB may be disrupted to form the blood-brain tumour barrier (BBTB). This leaky BBTB enables diagnosis of brain tumours by contrast enhanced magnetic resonance imaging; however, this disruption is heterogeneous throughout the tumour. Thus, relying on the disrupted BBTB for achieving effective drug concentrations in brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 215 publications
0
22
0
Order By: Relevance
“…Although various techniques have been developed to overcome the BBB and enable drug delivery, such as physical modalities (e.g., FUS and PEFs) [ 47 , 48 , 49 ], enhanced lipid- and water-solubility through drug design, as well as employing carriers and vectors [ 50 , 51 , 52 ], these strategies still fall short in outcomes. For instance, it has been reported that issues with reproducibility of FUS procedures can be an obstacle to its clinical use [ 53 ]. Mannitol, a cell-impermeable nontoxic alcohol, has been used successfully for reversible opening of the BBB in hyperosmotic concentrations, both experimentally and clinically [ 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although various techniques have been developed to overcome the BBB and enable drug delivery, such as physical modalities (e.g., FUS and PEFs) [ 47 , 48 , 49 ], enhanced lipid- and water-solubility through drug design, as well as employing carriers and vectors [ 50 , 51 , 52 ], these strategies still fall short in outcomes. For instance, it has been reported that issues with reproducibility of FUS procedures can be an obstacle to its clinical use [ 53 ]. Mannitol, a cell-impermeable nontoxic alcohol, has been used successfully for reversible opening of the BBB in hyperosmotic concentrations, both experimentally and clinically [ 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a common reason for the failure of PET neurotracers is limited brain entry due to low passive permeability and/or active export across the blood–brain barrier (BBB). In gliomas, the BBB is often partly disrupted, which results in increased permeability to hydrophilic contrast agents and enables tumor visualization by contrast-enhanced MRI [ 52 , 53 ]. However, BBB disruption shows significant intra- and inter-tumoral heterogeneity, and increased uptake of hydrophilic contrast agents is not necessarily predictive of the accumulation of lipophilic drugs or PET tracers [ 52 , 53 ].…”
Section: Considerations For the Development Of Midh-selective Pet-tra...mentioning
confidence: 99%
“…The BBTB, which is an abnormal, fenestrated and heterogenous variant of the BBB, permits the passage of contrast agents (allowing magnetic resonance imaging of GBM), although the permeability of drugs varies. It is assumed that the BBTB may support drug influx at the site of the tumor; nevertheless, it has also been shown that the accumulation of chemotherapeutics is often irregular, therefore limiting the efficacy of treatment [ 45 , 46 ]. Some of the proposed methods of overcoming this barrier include the usage of focused ultrasound techniques and microbubbles for mechanical opening of the BBB.…”
Section: Metal-based Nanoparticlesmentioning
confidence: 99%